Leadership and its Impact on Supervision in the Hospitality Industry - Patricia, Peprah; Peprah, Williams Kwasi (Archives of Business Research, 2023)
The hospitality industry has a high human capital requirement that depends on leadership to provide supervision for the utmost customer satisfaction. Based on this, this research looks at the impact of leadership on supervision among hotels in Ghana. This research was a causal research design. It investigated the correlational effect of leadership on supervision in the hospitality industry in Ghana. Data obtained from Ghana Tourism Authority’s National Data 2020 on Tourism Human Resource put the employees of 3 to 5 stars hotels as the study population at 7,347. The researcher used a Raosoft sample size calculator to determine a sample size of 366 at a 95% confidence level. A convenience sample technique was used to collect the data. Self-constructed instruments with Cronbach alpha of Leadership .710 and Supervision .751 were used to measure reliability. In answering the relationship question correlation analysis was used to establish the relationship. The study showed a highly positive significant relationship between leadership and supervision. It is recommended that abusive supervision by the leader should be monitored highly and controlled to motivate the supervisee to impact the hotel’s performance.